2014
DOI: 10.1371/journal.pone.0115772
|View full text |Cite|
|
Sign up to set email alerts
|

Electrical Stimulation over Bilateral Occipito-Temporal Regions Reduces N170 in the Right Hemisphere and the Composite Face Effect

Abstract: Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that can modulate cortical excitability. Although the clinical value of tDCS has been advocated, the potential of tDCS in cognitive rehabilitation of face processing deficits is less understood. Face processing has been associated with the occipito-temporal cortex (OT). The present study investigated whether face processing in healthy adults can be modulated by applying tDCS over the OT. Experiment 1 investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 89 publications
1
23
0
Order By: Relevance
“…Our overall finding also converges with recent tDCS research stimulating the occipitotemporal cortex (i.e., FFA and OFA) and modulating ERP components related to inverted and upright face processing (Yang et al, 2014). We also found some evidence that the effect of tDCS is primarily found at higher memory loads.…”
Section: Theoretical and Clinical Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Our overall finding also converges with recent tDCS research stimulating the occipitotemporal cortex (i.e., FFA and OFA) and modulating ERP components related to inverted and upright face processing (Yang et al, 2014). We also found some evidence that the effect of tDCS is primarily found at higher memory loads.…”
Section: Theoretical and Clinical Implicationssupporting
confidence: 90%
“…In most studies, between 1.0-2.0mA intensity direct current (DC) is administered by positioning electrodes in a manner intended to target brain regions of interest with anodal or cathodal polarity stimulation (Jacobson, Koslowsky, & Lavidor, 2012).A unidirectional flow of charge emanates from a single anode, propagates through cortical tissue, and returns via a single cathode;as anodal currentpropagates through the cortex, it produces neuronal membrane depolarization (Purpura & McMurtry, 1965),increases neuronal firing rates (Nitsche & Paulus, 2000, and increases functional brain connectivity intask-related networks (Peña-Gómez et al, 2012). Though tDCS has been used extensively in the behavioral, cognitive, clinical, and affective sciences literature (Jacobson et al, 2012;Price, McAdams, Grossman, & Hamilton, 2015;Shiozawa et al, 2014), very few studies have examined its influence on face processing or memory.In two of them, anodal tDCS was applied over the dorsolateral prefrontal cortex (Lafontaine, Theoret, Gosselin, & Lippe, 2013) or occipitotemporal cortex (which includes the FFA, the occipital face area (OFA), and superior temporal sulcus (Yang et al, 2014)), and outcomes were measured via event-related potentials (ERPs). In the first experiment, the authors found enhanced N170 repetition suppression, indicating faster face recognition with right hemisphere anodal stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The following left and right hemisphere ERPs were examined given that previous research has found these may play a key role in face processing: (a) P1 channels O1/O2, time range 70-160ms (e.g., Turano et al, 2016), (b) N170, T5/T6, 110-220ms (e.g., Turano et al, 2016), (c) N250, T5/T6, 220-310ms (Yang et al, 2014), (d) P600, P3/Pz/P4, 500-700ms (e.g., Düzel et al, 1997). For learning trials on the Adult and Infant Face Recognition Tests, grand-averages were computed for P1/N170 to measure early perceptual components.…”
Section: Eeg Recording and Processingmentioning
confidence: 99%
“…To date, few investigations have employed brain stimulation to understand the neural basis of the composite face illusion. However, a recent study employing the complete design found that transcranial direct current stimulation (tDCS) applied to occipito-temporal cortex reduced observers' susceptibility to the composite face illusion, relative to a sham condition (Yang et al, 2014; but see Renzi et al, 2015).…”
Section: Brain Stimulation and Neuropsychologymentioning
confidence: 99%